Mitigating Devices in Mosuli Iraqi Arabic With Reference To English - Hazem, Ali Hussein; Mohammad, Suha Idress (Ijaz Arabi Journal of Arabic Learning, 2021)
The Mosuli dialect is the dialect of the people of the city of Mosul in northern Iraq. It is one of the dialects of northern Mesopotamia, which is an extension of the Arabic dialects that prevailed in Iraq and the Euphrates Island in the Abbasid era. The Mosuli dialect, like other dialects of northern Mesopotamia, contains some of the ancient characteristics that are found in Standard Arabic, but it also has some unique features which distinguish it from the others. In comparison with the dialects of southern Mesopotamia, this dialect retains the features of urban dialects such as the letter qaaf. This study explores the most common uses, and the different types of expressions of mitigation used by people who speak the Mosuli Iraqi Arabic dialect in their everyday life in different situations. Mitigating devices are speech utterances used to lesson the force of the speech on the listener to avoid face-threatening situations. Although mitigating devices are widely used in writing and speaking, they have not been adequately investigated in previous studies. It is assumed that people use mitigation to lesson the force of direct speech. In order to prove this surmise, the data are collected from the native speakers of Mosuli Arabic dialect and analyzed according to Fraser’s 1981 model. The findings reveal that many participants use several expressions with the appropriate mitigating devices suited to different situations. More importantly, the findings show new ways of communication for those interested in the study of pragmatics in the Arabic language as well as English and in the language of other non-native speakers of Arabic.